The Species Composition and Biodiversity Indices of Spider Fauna in the Rice Field of Luong Phi Commune, Tri Ton District, An Giang Province - Minh Quang, Dinh; Thu, Tran Thi Anh; Tuan Khanh, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2, 2019)
Abstract: The study records 15 species belonging to 11 genera, 6 families based on the data analysis of 512 individuals collected during summer-autumn and autumn-winter seasons in the rice field both inside and outside the flood protection barrier in Luong Phi commune, Tri Ton district, An Giang province. Of these, Argiope dang , Clubiona coreana and Oxyopes sertatus belonging to Araneidae, Clubionidae, and Oxyopidae families, respectively, were firstly recorded for the spider-fauna in Vietnam. Clubiona sp., Erigone sp., Carrohtus sp. and Rhene sp. belonging to Clubionidae, Linyphiidae, and Salticidae families, respectively, were identified up to the genus level. Comprising 5 species, Araneidae was the largest family, followed by the family Salticidae with 4 species among the 15 identified species. That Araneus inustus and Oxyopes sertatus were found during summer-autumn and autumn-winter seasons, with the former of 257 individuals, shows that Araneus inustus was the most abundant species and could be the dominant species or the best-adapted species of the spider community. The number of species found in the autumn-winter season inside the barrier (9 species) was larger than that in summer-autumn season outside the barrier (5 species). Values of Margalef (d), Pielou (J’), Shannon-Weaver (H’) and Simpson (1-l) parameters were higher in the autumn-winter season inside the barrier than those in the summer-autumn season outside the barrier. This may be due to the difference in the use of agricultural components between these seasons. Argiope dang , Parawixia dehaani , Plexippus paykulli , Carrohtus sp. and Rhene sp. were found only outside the barrier, whereas Gasteracantha kuhli  and Evarcha pococki  were recorded only inside the barrier. The study concludes that the adaptability and the role of natural enemies of the two recorded species both inside and outside the barrier during the two rice crops, especially of the dominant species Araneus inustus, needs to be further studied. Keywords: An Giang, rice field, spider, Tri Ton. References [1] N.N. Đệ, Giáo trình cây lúa, Nxb Đại học Quốc gia Tp Hồ Chí Minh, Tp Hồ Chí Minh, 2008. [2] N.V. Viên, Sử dụng thuốc bảo vệ thực vật an toàn, hiệu quả, NXB Nông nghiệp, Hà Nội, 2015. [3] P.Đ. Sắc, P.T.H. Lưỡng, N.V. Quảng, Ảnh hưởng của nơi sống đến sự quần tụ của nhện (Araneae) ở khu vực nội đô của Hà Nội, Hội nghị côn trùng học quốc gia lần thứ 7, NXB Nông nghiệp, 2011, trang 240-245. [4] R.F. Foelix, Biology of Spider, Oxford University Press, second ed., New York, 1996. [5] R. Jocqué, A.S. Dippenaar-Schoeman, Spider families of the world, Royal Museum for Central Africa, Belgium, 2007. [6] N.V. Huỳnh, Nhện (Araneae, Arachnida) là thiên địch của sâu hại cây trồng, NXB Nông nghiệp, Thành phố Hồ Chí Minh, 2002. [7] T.T.A. Thư, Đ.M. Quang, N.H. Ly, Thành phần loài và đặc điểm phân bố của nhện (Araneae, Arachnida) ở Vồ Thiên Tuế - Núi Cấm, An Giang, Tạp chí Khoa học Đại học Đồng Tháp 4 (2017) 83-90. [8] L. Krogmann, J. Holstein, Preserving and Specimen Handling: Insects and other Invertebrates, in: I.M. Millar, V.M. Uys, R.P. Urban (eds), Collecting and preserving insects and arachnids, The Biosystematics Division, ARC – PPRI, South Africa, 2000, pp. 463-481. [9] H.W. Levi, D.E. Randolph, A key and checklist of American spiders of the family Theridiidae north of Mexico (Araneae), Journal of Arachnology 3 (1975) 31-51. [10] P.Đ. Sắc, Danh lục các loài nhện Việt Nam, NXB Khoa học tự nhiên và Công nghệ, Hà Nội, 2015.